A snapshot of parental involvement with homework and resultant parental perspectives on its value, efficacy and effects within the home. - Healy, Janette (My University, 2019)
Despite questions and concerns having been raised about the benefit and effects of homework in Ireland (IPPN, 2010; McMahon 2018), there is a “dearth of Irish research” (O’Toole, Kiely, McGillicuddy, O’Brien & O’Keeffe, 2019, p. 30) on the topic. For this reason, this study, which focuses on the mainstream primary school system, endeavours to generate insights into parental involvement with homework and resultant parental perspectives concerning its value, efficacy and effects within the home. A qualitative approach was utilised in the project, during which appropriate data was gathered by conducting semi-structured interviews with eleven parents whose children attend co-educational schools in Dublin in 2019. The findings indicate, that despite a lack of direction from schools, parents adopt a functional assistance role vis-à-vis their involvement with homework as their children mature through the primary school system. As a result of their engagement with the practice, parents value homework as a learning tool that has the capacity to improve children’s academic abilities. In addition, parents acknowledge homework’s benefit as a warning system that alerts them to any difficulties or deficiencies experienced by their children in the curriculum subjects throughout the school year, which in turn facilitates children receiving help at the optimal time to ameliorate these problems. Finally, parents believe that homework does not adversely affect the relationship between parent and child, even if it causes occasional stress. The proviso to this, however, is that the outcome may be different in the event that homework related stress is more consistent in nature. The study concludes by echoing a call for further research about homework in Ireland, with a focus on obtaining information about the levels of stress experienced during homework and the consequent effects of same.
Professional Master of Education (P.M.E.)
Keywords: Research Subject Categories